Meta-analysis of the Effect of the Discovery Model in Physics Learning on Critical Thinking Ability and Knowledge Competence of High School Students - Annisa N; Asrizal A; Fatni Mufit (Universitas Ahmad Dahlan, 2021)
21st Century Education requires students to have the competence and ability to think critically, especially in learning Physics. So we need an appropriate learning model, one of which is the discovery model. In fact, there are still many teachers who cannot choose the right learning model, so students cannot develop their competence and critical thinking skills. The solution is to analyze the effect of the discovery model on students’ critical thinking skills and knowledge competencies in terms of the type of discovery model and physics material. The articles were analyzed from 16 relevant articles originating from international and national articles. Based on the analysis that has been done, four research results were obtained. From the four research results, it is known that the discovery model in terms of the type of discovery model and physics material influences students’ critical thinking skills and knowledge competence.